BAG3 Genetic Cardiomyopathy May Overlap Fulminant Myocarditis Clinical Findings. (March 2022) - Jordà, Paloma; Martínez, Daniel; Farrero, Marta; Marcos, María Ángeles; Sandoval, Elena; Castel, María Ángeles; Pereda, Daniel; Quintana, Eduard; Arbelo, Elena; Sánchez, Aurora; Campuzano, Òscar; Tirón de Llano, Coloma; et al.
Abstract : Supplemental Digital Content is available in the text.